Diversity and community structure within anoxic sediment from marine salinity meromictic lakes and a coastal meromictic marine basin, Vestfold Hills, Eastern Antarctica - John Bowman; Rea, SM; Sharee McCammon; Thomas McMeekin (2000)
16S rDNA clone library analysis was used to examine the biodiversity and community structure within anoxic sediments of several marine-type salinity meromictic lakes and a coastal marine basin located in the Vestfolds Hills area of Eastern Antarctica. From 69 to 130 (555 total) 16S rDNA clones were analysed from each sediment sample, and restriction fragment length polymorphism (RFLP) and sequence analysis grouped the clones into 202 distinct phylotypes (a clone group with sequence similarity of >0.98). A number of phylotypes and phylotype groups predominated in all libraries, with a group of 10 phylotypes (31% of clones) forming a novel deep branch within the low G + C Gram-positive division. Other abundant phylotypes detected in several different clone libraries grouped with Prochlorococcus cyanobacteria, diatom chloroplasts, delta proteobacteria (Desulfosarcina group, Syntrophus and Geobacter/Pelobacter/Desulphuromonas group), order Chlamydiales (Parachlamydiaceae) and Spirochaetales (wall-less Antarctic spirochaetes). Most archaeal clones detected (3.1% of clones) belonged to a highly diverged group of Euryarchaeota clustering with clones previously detected in rice soil, aquifer sediments and hydrothermal vent material. Little similarity existed between the phylotypes detected in this study and other clone libraries based on marine sediment, suggesting that an enormous prokaryotic diversity occurs within marine and marine-derived sediments.